A case of pancreatic schwannoma showing increased FDG uptake on PET/CT. (2017) - Fukuhara, Sotaro; Fukuda, Saburo; Tazawa, Hirofumi; Imaoka, Kouki; Mochizuki, Tetsuya; Hirata, Yuzo; Fujisaki, Seiji; Takahashi, Mamoru; Nishida, Toshihiro; Sakimoto, Hideto
Highlights: Pancreatic schwannoma is rare and preoperative diagnosis is difficult due to the lack of specific symptoms, radiological characteristics and tumor markers. Incidental detection of pancreatic schwannoma is predicted to increase due to the widespread use of CT and MRI. It is important to take into account this tumor in the differential diagnosis of pancreatic tumors. We should be aware that FDG-PET/CT shows abnormal accumulation in a benign pancreatic schwannoma. Abstract: Introduction: Schwannomas are neoplasms originating from Schwann cells in nerve sheath, but pancreatic schwannomas are rare. Presentation of case: A 59-year-old female incidentally pointed out a 2-cm-sized solid mass in the pancreas head by computed tomography (CT) which was performed for other reasons. Magnetic resonance imaging (MRI) showed a mass with hypointensity on T1-weighted images and a heterogenous hyperintensity on T2-weighted images. Magnetic resonance cholangiopancreatography (MRCP) showed no abnormal findings in the main pancreatic duct. The mass of the pancreas head showed a significantly increased uptake on fluorin-18 fluorodeoxyglucose positron emission tomography CT (FDG-PET/CT). Based on the radiological findings, a malignant potential tumor was preliminarily considered. Subtotal stomach-preserving pancreatoduodenectomy (SSSPD) was performed to make a definite diagnosis. The resected specimen showed a well-encapsulated circumscribed mass, measuring 2.0 cm, in the pancreas head. Histopathological examination revealed proliferation of spindle cells showing interlacing and palisading patterns in the tumor. The proliferating cells showed no atypia and few mitoses. Immunohistochemically, the spindle cells were positive for S-100 protein. The Ki67 labeling index was approximately 2%. Based on these findings, a diagnosis of benign schwannoma of the pancreas was made. Conclusion: Although pancreatic schwannoma is a rare neoplasm, it is important to take into account this tumor in the differential diagnosis of pancreatic tumors. In addition, we should be aware that FDG-PET/CT shows abnormal accumulation in a benign pancreatic schwannoma.